Cultural Adaptation and Psychometric Validation of the Simplified Chinese Version of the Fear Avoidance Component Scale (FACS) - Zhongyi Tu; Junfang Miao; Yanzhao Zhang; Zhaohui Yang; Rui Xu; Randy Neblett (Pain Research and Management)
Conclusions: The FACS-Chi demonstrated good psychometric properties, including excellent test-retest reliability and internal consistency and satisfactory construct validity. The FACS-Chi may be a useful measure of pain-related FA in Chinese-speaking patients with chronic musculoskeletal pain.